2017 CVM News: Reindeer helps save younger brother from devastating illness - Office of Marketing and Communications. Media Relations (Cornell University, College of Veterinary Medicine, 2017)
This news item is about: Some reindeer live a bit south of the North Pole. In Shortsville, N.Y., about 30 miles east of Rochester, reindeer brothers Moose and Little Buddy call a little farm home. Their owner Mike Schaertl was looking forward to Little Buddy’s first holiday season, but last month, the five-month-old reindeer got very sick. Reindeer are vulnerable to tick borne diseases and living in areas where deer graze can increase the risk of infection. When Little Buddy lost his energetic personality and had no interest in eating his favorite beet pulp or playing with Moose, concern grew.